PENGARUH PRUDENCE DAN INTELEKTUAL CAPITAL TERHADAP MANAJEMEN LABA DENGAN VARIABEL KOMITE AUDIT SEBAGAI VARIABEL MODERASI - Halimahtussakdiah Halimahtussakdiah; Sanusi Ariyanto; Alfi Nopriyanti (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the influence of prudence and intellectual capital on earnings management, with the audit committee serving as a moderating variable. The research adopts a quantitative approach using regression analysis to examine data from companies listed on the Indonesia Stock Exchange. The results indicate that prudence has a positive and significant effect on earnings management practices, meaning that companies that are more cautious in managing profits tend to avoid earnings manipulation. On the other hand, intellectual capital does not have a significant impact on earnings management, suggesting that an increase in knowledge and innovation within the company does not necessarily reduce earnings management practices. Furthermore, the audit committee has been proven to strengthen the effect of prudence on earnings management but does not strengthen the effect of intellectual capital on earnings management. These findings highlight the important role of the audit committee in overseeing and enhancing the transparency of financial reporting while ensuring compliance with applicable accounting principles.